2004
DOI: 10.1121/1.1795335
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of vowel normalization procedures for language variation research

Abstract: An evaluation of vowel normalization procedures for the purpose of studying language variation is presented. The procedures were compared on how effectively they ͑a͒ preserve phonemic information, ͑b͒ preserve information about the talker's regional background ͑or sociolinguistic information͒, and ͑c͒ minimize anatomical/physiological variation in acoustic representations of vowels. Recordings were made for 80 female talkers and 80 male talkers of Dutch. These talkers were stratified according to their gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
212
2
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(242 citation statements)
references
References 31 publications
(12 reference statements)
7
212
2
11
Order By: Relevance
“…In order to minimize physiological differences between participants so that the analysis can focus on speech production differences in dialect and style, it is necessary to normalize the vowel formants. As per Adank, Smits, and van Hout (2004), the Lobanov normalization method was used (Lobanov 1971).…”
Section: Discussionmentioning
confidence: 99%
“…In order to minimize physiological differences between participants so that the analysis can focus on speech production differences in dialect and style, it is necessary to normalize the vowel formants. As per Adank, Smits, and van Hout (2004), the Lobanov normalization method was used (Lobanov 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Dutch production task Figure 4 presents the spectral properties in terms of F1 and F2 of the Dutch vowels produced by the Ghent and Antwerp speakers. All vowels were normalized using the Lobanov normalization method (Lobanov 1971), since it has been shown that this method is effective in eliminating physiological sex-related differences, while preserving regional differences (see Verhoeven and Van Bael 2002a, 2002band Adank et al 2004b). …”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to consider the fact that formant locations are influenced not only by the phonemic quality but also by the anatomical/physiological characteristics of the speaker such as vocal tract length and shape. Some vowel normalization methods are effective in reducing speaker differences in terms of anatomical/physiological variations while largely preserving phonemic and socio-linguistic variations [4]. This property of the normalization procedures is instrumental in our native -non-native classification.…”
Section: Formant Space Based Methodsmentioning
confidence: 99%
“…Vowel-extrinsic normalization procedures use the knowledge of the formants of all the vowels of the speaker. In research investigating language variation [4], vowelextrinsic formant-intrinsic normalization procedures have been found effective in reducing differences due to physiological variations while at the same time preserving phonemic and socio-linguistic variation.…”
Section: Formant Space Based Methodsmentioning
confidence: 99%
See 1 more Smart Citation